Navigation and Control of Autonomous Marine Vehicles - Sharma, Sanjay (Associate professor in intelligent autonomous control systems); Subudhi, Bidyadhar, 1963- (IET transportation series ;, 2019)
This book covers the current state of research in navigation, modelling and control of marine autonomous vehicles, and deals with various related topics, including collision avoidance, communication, and a range of applications.